Badanie satysfakcji jako atrybutu jakości systemów e-usługowych - Karol Łopaciński; Leszek A. Maciaszek (Problemy Zarządzania, 2015)
Due to the growing demand for different types of e-services there are more and more systems that allow for e-services provision and management on the market. The quality of such solutions should be improved in cooperation with customers on the basis of information about the level of their satisfaction with the usage. This can be possible owing to regular user satisfaction research. The article presents the concept of estimating satisfaction with e-service software which is based on the achievements of marketing research and software quality studies.